Efecto de la administración de salbutamol sobre el comportaminero productivo de pollos de carne linea Cobb 500 en la etapa de acabado utilizando dos dietas con diferentes niveles nutricionales - Castro Li, Catherine Evelyn (2006)
The present investigation has the purpose of determining the effect of the administration of salbutamol on the productive behavior of broilers line cobb 500 in the ended up stage of using two diets with different nutritional levels. One hundred twenty broilers of 34 days of age with an initial weight of 1.81 kg were used in his finishing phase, they were distributed at random under a design completely to the randomized one in the following treatments: T1 (standard ration), T2 (standard ration + 4 mg of salbutamol / kg Food), T3 (ration of greater nutritional density + 4 mg of salbutamol / kg of food), and T4 (ration of greater nutritional density) and evaluated in the parameters of gain of weight, food comsumption, nutritional conversion, merit economic yield of housing and amount of fat. After 10 days that were put under the treatment, the total increases of weight alive and final weight were 1.01 and 2.81 kg. In T1; 0.91 and 2.72 kg. In T2; 1.02 and 2.85 kg. In T3; 1.12 and 2.92 kg. In T4. obtaining Significant differences (p> 0.05) Abdominal and cervical fat contained 94.7 gr, 68.2 gr, 78.7 gr, 97.5 gr. in the same order of treatments. The food consumption registered by animal during the experiment was in T1 = 2.37 kg; T2 = 2.11 kg; T3 = 2.17 kg; T4 = 2.40kg. Their corresponding nutritional conversions and the economic merit were 2.35 and 2.34; 2.15 and 2.25; 2.13 and 2.31; 2.15 and 2.22